Degradation of textiles dyes and scavenging activity of spherical shape obtained anatase phase of Co–Ni-doped TiO2 nanocatalyst - Thakur, Nikesh; Thakur, Naveen (Journal of materials science. Materials in electronics, 2024)
Dye contamination in water is a global concern due to its harmful impact on human health and aquatic ecosystems. Particularly, the textile industry contributes hazardous colored pollutants that often find their way untreated into nearby natural water bodies. Among various methods, photocatalysis stands out as the most effective solution for addressing dye pollution, with titanium dioxide (TiO 2 ) being a leading photocatalyst due to its exceptional capability for dye removal from wastewater. To enhance the efficiency of dye degradation under UV light, extensive research has focused on augmenting TiO 2 efficiency through doping and altering its morphology. In this study, the anatase phase of cobalt–nickel (Co–Ni)-doped TiO 2 nanoparticles (TNPs) was synthesized using both chemical and green methods, employing a microwave-assisted technique. These methods incorporated polyvinylpyrrolidone (PVP) and Tinospora Cordifolia ( T. Cordifolia ) for chemical and green encapsulation, respectively. Various physicochemical attributes of the encapsulated Co–Ni-doped TNPs were analyzed through a range of characterization spectroscopy. The encapsulated NPs exhibited tetragonal crystal structure and spherical morphology with particle size ranging from 17 to 24 nm. During the evaluation of their photocatalytic performance toward methyl orange (MO) and methylene blue (MB), it was noted that as the dosage of NPs catalysts increased, the degradation rate also showed an augmentation when exposed to UV radiation. About 100% value for degradation was noted for MO and MB dyes'. Furthermore, encapsulated Co–Ni-doped NPs displayed significant antioxidant activity, with efficacy upto 93% for DPPH assay.